Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1111/j.1524-4733.2008.00472.x
|View full text |Cite
|
Sign up to set email alerts
|

Costs of First-Line Doublet Chemotherapy and Lifetime Medical Care in Advanced Non–small-Cell Lung Cancer in the United States

Abstract: There is a cost differential between first-line doublet regimens in terms of lifetime and on-treatment costs. Although doublet therapy with platinum and a taxane was the most frequently utilized regimen, it was associated with the highest lifetime and on-treatment costs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 17 publications
(18 reference statements)
0
11
0
1
Order By: Relevance
“…Also, more recent increases in spending for advanced lung cancer may reflect not only changes in detection and staging techniques and management over time, but also increased use of chemotherapy and targeted therapies. Three studies were identified that examined the cost of advanced lung cancer using the linked SEER-Medicare claims data [4,7,9]. Yabroff and colleagues reported that costs of care during the last year of life among patients with distant lung cancer averaged $85,392 (in 2010 USD); hospitalization costs were the single largest component of cost among these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, more recent increases in spending for advanced lung cancer may reflect not only changes in detection and staging techniques and management over time, but also increased use of chemotherapy and targeted therapies. Three studies were identified that examined the cost of advanced lung cancer using the linked SEER-Medicare claims data [4,7,9]. Yabroff and colleagues reported that costs of care during the last year of life among patients with distant lung cancer averaged $85,392 (in 2010 USD); hospitalization costs were the single largest component of cost among these patients.…”
Section: Discussionmentioning
confidence: 99%
“…While a few retrospective longitudinal studies [7-11] have estimated the cost of metastatic lung cancer in the US, these studies employed varied designs and methods (i.e., in terms of patient populations, disease definitions, and measure of healthcare costs), did not track lifetime healthcare resource use and costs, or did not analyze cost components by setting or type of service. Up-to-date data on resource use and costs among patients with metastatic lung cancer -- overall and by constituent component -- thus may help inform current decision-making about the optimal allocation of healthcare resources.…”
Section: Introductionmentioning
confidence: 99%
“…Other aNSCLC studies reported costs of first-line therapy ranging from US$22,126 to US$31,104 [8] and US$28,562-34,516 [7] versus US$84,671 in this study. The costs results from the earlier studies are based primarily on chemotherapy doublet regimens for Medicare patients prior to 2004.…”
Section: Research Article Henk and Raymentioning
confidence: 91%
“…The most recent real-world estimates of the cost of systemic treatment of aNSCLC in the USA are based primarily on data from 1998 to 2006 [6][7][8]. These studies either did not distinguish costs by treatment regimen [6] or were limited to first-line therapies (primarily platinum-based doublets) commonly prescribed during that period [7,8].…”
Section: Research Article Henk and Raymentioning
confidence: 99%
See 1 more Smart Citation